Facilitating nitrogen accessibility to boron-rich covalent organic frameworks via electrochemical excitation for efficient nitrogen fixation - Sisi Liu (Nature Portfolio, 2019)
Covalent organic frameworks are potential catalysts for nitrogen reduction, but limited nitrogen transport restricts the utilization ratio of active sites. Here, the authors demonstrate that electrochemical excitation of covalent organic frameworks can lead to efficient nitrogen reduction.